China's foreign policy who makes it, and how is it made? - Rozman, Gilbert (Palgrave Macmillan, 2013)
The May 19-20, 2011 Asian conference provided a venue to reassess foreign policy decision-making in China. The goal of the institute is not only to offer policy solutions but also to train experts in public diplomacy and related fields in order to strengthen Korea's capacity to better tackle some of the most pressing problems affecting the country, the region and the world today.